(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Many of the financial instruments mutual fund is one of the most attractive financial investment instrument that plays a vital role in the economy of a country. The present paper investigates the performance of 15 open-ended, growth-oriented equity schemes for the period from April 2011 to March 2016 (five years) of transition economy. The study used the monthly NAV of different schemes to calculate the returns from the fund schemes. BSE-Sensex has been used for market portfolio. The results of the study concluded that all the schemes have represented positive returns. The maximum return was from DSP-BR Micro Cap Funds (G) and Reliance Small Cap Fund (G) and minimum return was from Sundaram SMILE Fund – IP (G) and Sundaram Select Midcap – IP (G). In the context of Risk, it is observed that out of 15 schemes, only 1 scheme have registered a beta value greater than one indicated that they belonged to more risk category. The remaining 14 schemes have registered beta less than one which indicated that they belonged to low risk category.